Digital participation and digital divides in a former socialist country - Allaste, A.; Cairns, D. (Young people's participation: Revisiting youth and inequalities in Europe, 2021)
This chapter discusses the issue of youth digital participation. Social media in particular is thought to be able to open up new means of being political, albeit with strong criticism of participation via this means also noted. The chapter focuses on this theme of digital participation in Estonia, a country labelled as the ‘first digital nation’, that also has the legacy of being a former socialist country with limited levels of civic engagement and variable levels of participation between different groups of young people. The chapter hence analyses how young people politically engage through the internet, and how differences persist between those who use the internet for politics and those who do not. Empirical evidence is taken from a large-scale European project, MYPLACE (Memory, Youth, Political Legacy and Civic Engagement), which gathered data from two contrasting sites within Estonia, thus enabling us to make contrasts between different youth digital participation experiences.